Development and assessment of a self-management intervention for urinary incontinence among patients with prostate cancer: protocol for a randomized feasibility study - Ching Hui Chien; Kuan Lin Liu; Chun Te Wu; Cheng Keng Chuang; Kai Jie Yu; Po Hung Lin; Xuan Yi Huang; See Tong Pang (BMC Urology, 2023)
Abstract Background Urinary incontinence is a common complication among patients with prostate cancer who have undergone radical prostatectomy. Guided by social cognitive theory and a framework for the recovery of health and well-being, we propose to develop and test a self-management intervention for patients with prostate cancer who experience urinary incontinence after undergoing radical prostatectomy. Methods In this study, a self-management intervention for urinary incontinence (SMI-UI) is developed, comprising a mobile self-management application, a self-management handbook, and professional support. The feasibility, acceptability, and effectiveness of this intervention will be assessed. Patient data from the urology departments of two hospitals will be collected through convenience sampling by adopting an experimental, parallel, and random assignment research design. Patients experiencing urinary incontinence after undergoing radical prostatectomy will be invited to participate. After completing the pretest questionnaire, patients will be randomly divided into the experimental and attention control groups. The experimental group will undergo a 12-week SMI-UI, whereas the attention control group will receive an intervention consisting of a single dietetic education information package. The two groups will be tested 12 and 16 weeks after the pretest. In this study, we recorded the sociodemographic and clinical variables; recruitment rate; retention rate; satisfaction with the intervention; cancer-related self-efficacy; urination symptoms and disturbance; social participation and satisfaction; resilience; and demoralization. Trial Registration ClinicalTrials.gov ID: NCT05335967 [date of registration 04-04-2022].